FOREIGN LANGUAGE PLANNING AND POLICY IN INDONESIA: PROBLEMS AND CHALLENGES - M. Kharis; Suwarno Imam Samsul; Mintowati Mintowati; Anas Ahmadi (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2020)
Studies on foreign language planning and policy are still scarce because their determination is a complex process and related to various forces and interests. Foreign languages become international communication and a medium of intellectual and social actualization. However, foreign language competences are still a problem for most academics for international publication. Thus, policies and planning for foreign language are essential requirements to answer the challenges of this era and in the context of self-development.Keywords: Planning, policy, foreign language learning